(untitled) (Scientific journal of the Fergana State University, 2023)
The article presents a new compound synthesized on the basis of natural cyanoglycoside-amygdalin and m-ferrocenyl benzoic acid. Some physical and chemical parameters of the new substance and the IR spectrum characterizing the structure were also studied.